The contribution of field trips to learning: Greek teachers’ beliefs - Zotou, Evaggelia (International Journal of Educational Studies, 2025)
The aim of this study is to investigate Greek senior high school teachers’ beliefs as far as the contribution of field trips to learning is concerned and analyze their impact on learning. The findings suggest that trip fields are viewed as an important learning experience by teachers. Hence, school communities should promote their implementation by all means and teachers’ positive attitude towards field trips certainly reinforces students’ learning skills and motivation.